Operating System : Daniel G. Andujar, Technologies To The People. - Borja-Villel, Manuel; Lillemose, Jacob; Dressler, Iris; de la Cueva, Javier; Pardo, José Luis; Cuenca, Alberto Lopéz; Medina, Isidoro Valcarcel; Museo Nacional, Centro de arte Reina Sofia, Madrid (Madrid : Museo Nacional, Centro de arte Reina Sofia, 2015)
Andujar, Daniel G.
Operating System, Museo Nacional Centro de arte Reina Sofia, Madrid, 21.01.2015 - 04.05.2015
kunstcatalogus